2020
DOI: 10.1007/s40820-020-00539-6
|View full text |Cite
|
Sign up to set email alerts
|

MOF-Derived CoSe2@N-Doped Carbon Matrix Confined in Hollow Mesoporous Carbon Nanospheres as High-Performance Anodes for Potassium-Ion Batteries

Abstract: In this work, a novel vacuum-assisted strategy is proposed to homogenously form Metal–organic frameworks within hollow mesoporous carbon nanospheres (HMCSs) via a solid-state reaction. The method is applied to synthesize an ultrafine CoSe2 nanocrystal@N-doped carbon matrix confined within HMCSs (denoted as CoSe2@NC/HMCS) for use as advanced anodes in high-performance potassium-ion batteries (KIBs). The approach involves a solvent-free thermal treatment to form a Co-based zeolitic imidazolate framework (ZIF-67)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…40 The C 1s spectrum could be fitted to several peaks at 284.0, 284.6, 285.6, and 288.5 eV, which were assigned to C═C, C C,C O, and O C═O bonds, respectively, as displayed in Figure 6C. 41,42 Furthermore, in the Raman spectrum of NiSe x @C, the two peaks located at 1354 and 1602 cm À1 corresponded to the D band (related to disordered characteristics) and G band (related to graphitic characteristics), respectively, as shown in Figure 6D. [43][44][45][46] The I D /I G ratio (0.99) suggested that the carbon in the carbon nanospheres was partially graphitized by post-treatment at 700 C. 47,48 The thermogravimetric (TG) curves of NiSe x @C and bare NiSe x are represented in Figure S7.…”
Section: Resultsmentioning
confidence: 97%
“…40 The C 1s spectrum could be fitted to several peaks at 284.0, 284.6, 285.6, and 288.5 eV, which were assigned to C═C, C C,C O, and O C═O bonds, respectively, as displayed in Figure 6C. 41,42 Furthermore, in the Raman spectrum of NiSe x @C, the two peaks located at 1354 and 1602 cm À1 corresponded to the D band (related to disordered characteristics) and G band (related to graphitic characteristics), respectively, as shown in Figure 6D. [43][44][45][46] The I D /I G ratio (0.99) suggested that the carbon in the carbon nanospheres was partially graphitized by post-treatment at 700 C. 47,48 The thermogravimetric (TG) curves of NiSe x @C and bare NiSe x are represented in Figure S7.…”
Section: Resultsmentioning
confidence: 97%
“…5k shows the electrochemical impedance spectrum (EIS) of the CoSe 2 @NC/MWCNTs electrode at different electrochemical states during the first discharge/charge cycle. Based on the fitting results of ex situ EIS (Table S4†), the values of R ct gradually decreased during the sodiation, which might be due to the formation of ultrafine Co. 64 When charging, the impedance undergoes a negligible change, implying that the CoSe 2 @NC/MWCNTs electrode is quite stable in the (de)sodiation process.…”
Section: Resultsmentioning
confidence: 98%
“…During the initial discharging, R tot exhibited a continuous decrease, which could be a reflection of the transition between large crystals and ultrafine nanocrystals, as verified by the HR-TEM image (Figure 5B). 47 In the subsequent charging, R tot increased as the depotassiation proceeded. This resistance increase was due to the structural strain caused by the phase transformation to ZnSe nanocrystals.…”
Section: Resultsmentioning
confidence: 98%
“…The decreasing tendency continued to 1.0 V owing to the SEI nucleation as a stable surface deposit. 47 After 1.0 V, D K+ exhibited an increasing trend, because of the generation of ultrafine KZn 13 and K 2 Se nanocrystals. 47 The diffusion coefficient decreased as the depotassiation proceeded, which was related to the increase in R tot corresponding to the structural strain during the phase transformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation